Fiscal Rules and Countercyclical Policy : Frank Ramsey Meets Gramm-Rudman-Hollings - Tanner, Evan (IMF Working Papers; Working Paper, 2003)
Fiscal rules-legal restrictions on government borrowing, spending, or debt accumulation (like the Gramm-Rudman-Hollings Act in the United States)-have recently been adopted or considered in several countries, both industrial and developing. Previous literature stresses that such laws restrict countercyclical government borrowing, thus preventing intertemporal equalization of marginal deadweight losses of taxation-an idea associated with Frank Ramsey. However, such literature typically abstracts from persistent current deficits that are financed by future tax increases. Eliminating such deficits may substantially reduce tax rate variability-the very goal of countercyclical borrowing-even over a finite horizon. Thus, Gramm-Rudman-Hollings and Frank Ramsey are not necessarily enemies and they may even be good friends!.